Rezension von: Heinrich, Jörg (Hrsg.), Kaufbuch Cannstatt 1555–1582 - Wille, Wolfgang (Zeitschrift für Württembergische Landesgeschichte, 2019)
Jörg Heinrich (Hg.), Kaufbuch Cannstatt 1555 – 1582, Berlin: Verlag Jörg Heinrich 2016. 532 S., € 35,–